REHABILITATION OF PATIENTS WITH CORONARY HEART DISEASE AFTER CORONARY ARTERY BYPASS GRAFTING AT THE STATIONARY STAGE - Tatiana Krasavina; Victoria Zaborova; Irina Lazareva; Kseniya Yurku; Victor Putilo; Victoria Gameeva; Mark Ivanov; Dilyana Vicheva; Vladimir Stavrev (Peytchinski Publishing, 2023)
Purpose: To study the application of low-intensity physical veloergometric loads according to a special method in the system of rehabilitation of coronary heart disease patients (CHD) after coronary bypass (CB) at the hospital stage. Materials and Methods: We examined 84 patients (men) with CHD who underwent CB surgery: main group (n=52), the average age of 48.4 ± 0.8 years, the control group (n=32), the average age of 47.9 ± 1.11. All patients of the main group underwent exercises on a bicycle ergometer. The control group underwent rehabilitation without training but with a complex of therapeutic exercises. The following indicators are evaluated: the power of the threshold load in watt, Double product (DP), electrocardiography (ECG), heart rate (HR), respiratory rate (RR), blood pressure (BP). Results: Training sessions on a bicycle ergometer, according to a special technique, can be carried out as a method of rehabilitation at the stationary stage, rehabilitation center, at home. The best is the effect of training in the group of patients involved in the clinic before surgery and immediately after surgery with continued classes for a year. Conclusions: Analysis of the remote results shows that the use of physical training on this method makes it possible to improve the function of the myocardium and improve the prognosis of the disease.